Prevalence of fungal infections that cause tinea pedis in farmers in Tegalharjo Banyuwangi - Fitrotin Azizah; Anindita Riesti Retno Arimurti; Ruspeni Daesusi; Dellanis Arina Putri (Bioma : Jurnal Ilmiah Biologi, 2022)
Tinea pedis is a type of superficial mycosis. Tinea pedis is a dermatophyse that is most often found in humans and is usually called water fleas. Lack of maintaining cleanliness and wearing closed shoes is one of the factors that causes Tinea pedis. Tinea pedis usually affects adults who work in wet or humid places, such as car and motorcycle washers, garbage collectors and farmers. When doing activities, the average farmer uses boots for too long. However, some farmers who do not wear boots while working experience itching on the soles of their feet. This research aims to determine the prevalence of fungal contamination that causes water fleas (Tinea pedis) in farmers in Tegalharjo village, Banyuwangi Regency. The population of this research are 30 farmers in Tegalharjo village, while the research sample Is skin scrapings between the toes of the farmers. Then the sample obtained is directly examined by using a microscope and 10% KOH reagent. The results shows that the farmers who are contaminated with the fungus that caused Tinea pedis are 6 people with a percentage (20%) and 24 people who are not contaminated with a percentage (80%). The incidence of infection Tinea Pedis among farmers in Tegalharjo Village, Banyuwangi Regency is also influenced by the duration of working in a day and the habit of wearing boots.